The potential applicability of blockchain in the Thai retail supply chain - ๊Udomchalermdej, Piyamas (2019)
Background & Purpose: Under the market challenges, supply chain management is becoming more complex and inefficient. An effective supply chain management and sustainable business practices lead the companies to stand out over the competitors. Blockchain technology has potentially revolutionized businesses. Companies would benefit to improve overall performance through the blockchain. This management project aims to evaluate the applicability of blockchain technology in retail supply chain management in the context of Thailand.